Academic Library Instruction, Evidence-Based Practice, and Social Workers: An Exploratory Survey. Issue 4 (2nd October 2017) - Pendell, Kimberly; Kimball, Ericka
Abstract: When social work students graduate and move into their professional practice, they also move into a vastly different information landscape than that of the academic environment. To better understand the use of evidence-based practice (EBP) and information sources in practice, the authors performed a national survey of social workers. This survey provides a snapshot of how frequently social workers employ EBP, their use of research articles and other information resources, and their prior library instruction. The researchers make recommendations for increased consideration of the practice environment in library instruction, open access advocacy, and outreach to the field.